Healthcare Utilization Under a Comprehensive Public Welfare Program: Evidence From Japan - Yuda, Michio (Frontiers in Public Health, 2022)
The public assistance system in Japan provides detailed and comprehensive livelihood support for low-income families with various needs, and the beneficiaries of the public welfare program in Japan can receive the same medical treatments as those insured of the universal public health insurance without any financial burdens. This system has greatly contributed to maintaining and improving the health of PA beneficiaries but may cause excessive health care utilization: moral hazard. This study uses a large sample taken from two nationally representative claim data for public assistance and public health insurance patients to estimate the magnitude of moral hazard effect in basic outpatient utilization. The results of the fixed-effect regression analysis utilizing the concept of pseudo panel data analysis and those of propensity score matching show that the average treatment effect of public assistance assignment on health care utilization are significantly positive. Specifically, public assistance assignment increases monthly health care expenditure by 17.5 to 22.9 percent and the monthly number of doctor visits by 23.1 to 27.8 percent, respectively. In addition, the average treatment effects on the treated are also significantly positive, suggesting that monthly health care expenditure significantly decreases by 22.7 to 25.0 percent and the number of visits by 27.6 to 29.7 percent, respectively, when imposing a copayment on PA beneficiaries. However, the estimated price elasticity based on these results is very small, approximately -0.02, indicating that the level of copayment rate has little effect on health care utilization.